2019
DOI: 10.1108/compel-09-2018-0372
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity studies and optimization of arrangements of optically pumped magnetometers in simulated magnetoencephalography

Abstract: Purpose The purpose of this paper is to present a simulation study using a model of a new optically pumped magnetometer sensor for application in the field of magnetoencephalography. The effects of sensor distance and orientation on the measurement information and the sensitivity to neuronal sources are investigated. Further, this paper uses a combinatorial optimization approach for sensor placement to measure spontaneous activity in the region of the occipital cortex. Design/methodology/approach This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…This led us to use the ABC 160 system, whose inter electrode/sensor distance allows for a full OPM array. Additional computations (Figure S1) have shown that the effect of rotating the tangential axis is negligible for whole‐head systems, in line with other studies (Eichardt et al, 2019). This flexibility in the sensor orientation facilitates the assemble of high density OPM arrays, and therefore worth exploiting.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This led us to use the ABC 160 system, whose inter electrode/sensor distance allows for a full OPM array. Additional computations (Figure S1) have shown that the effect of rotating the tangential axis is negligible for whole‐head systems, in line with other studies (Eichardt et al, 2019). This flexibility in the sensor orientation facilitates the assemble of high density OPM arrays, and therefore worth exploiting.…”
Section: Discussionsupporting
confidence: 90%
“…Even more, this approach seems better suited for practical applications in which the number of sensors available at any moment may vary due to technological glitches, as we have personally experienced with state‐of‐the‐art OPMs. The use of a more thorough methodology, such as combinatorial multilevel optimisation (Eichardt et al, 2019), is planned for future development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliable imaging of the brain for diagnostic purposes is a very significant procedure, as the early detection of possible anomalies is deemed decisive for a successful therapy. Several defects and malfunctions in the brain’s inner structure can be spotted through various non-invasive imaging techniques (Oldendorf, 1978; Wintermark et al , 2005; Shenton et al , 2012; Kraiger and Schnizer, 2013; Zhang et al , 2014; Szajerman et al , 2018; Eichardt et al , 2019) either considering the different properties of the brain tissues or through the brain activity. The former includes the popular magnetic resonance imaging (MRI) and the computed tomography (CT) scanning, while the latter is implemented in terms of functional MRI (fMRI), positron emission tomography (PET), electroencephalography (EEG) and magnetoencephalography (MEG).…”
Section: Introductionmentioning
confidence: 99%